Peningkatan Prestasi dan Kemandirian Belajar Matematika Melalui Model Pembelajaran STAD Menggunakan Media Berbasis Aplikasi Canva - Azzahra, Fatimah; Muslim, Arifin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study was conducted to apply the STAD (Student Team Achievement Division) type cooperative learning model using Canva application-based media to improve achievement and independence in learning media-assisted mathematics through Canva applications for fourth-grade students of SDN Gunungmujil. The procedure used in this research is classroom action research consisting of 2 cycles where each cycle consists of planning, implementation, observation, evaluation, and reflection stages. The assessment instruments used in this research are teacher observation sheets and student observation sheets, as well as evaluation questions, while LKPD is used during discovery activities. The results of cycle I and cycle II showed that the level of learning completeness increased by 73.83% and 93.36%, respectively. The increase in the level of learning completeness was accompanied by an increase in classical learning achievement, at least 75% of students achieved a score ≥ 70. The results of the research on student learning independence also showed an increase from cycle I of 61.07% and the results of cycle II to 86.25%. The conclusion of this research is that there is an increase in learning achievement and learning independence of students using the STAD-type cooperative learning model through Canva application-based media. STAD model learning must continue to be implemented to improve the achievement and learning independence of elementary school students. Keywords: Learning Independence, Canva Application Based Media, STAD Learning Model, Learning Achievement